Investigating Beliefs, Attitudes and Motivation toward English Language Learning among Thai and Chinese Undergraduate Students in Different Study Programs - Sun, Lu-Geng; Wudthayagorn, Jirada (LEARN Journal: Language Education and Acquisition Research Network, 2024)
This study investigated the beliefs, attitudes, and motivation of Thai and Chinese undergraduate students in relation to English language learning. Utilizing a mixed-method, explanatory sequential design, it aims to provide a better understanding of the three variables mentioned above. The quantitative data analysis showed disparities between the cohorts, with Chinese undergraduate students often displaying more robust orientations. However, the qualitative data analysis showed that both groups valued immersive learning experiences and technological integration. The research advocates for pedagogical frameworks in English education that align with overarching global paradigms while respecting individual cultural nuances. Such revelations are important for refining teaching practices and curricula to enhance genuine global literacy. It is also recommended that future research efforts diversify their cultural purview and give due consideration to variations in socio-economic contexts.